Integrating Natural Nest Characteristics into the Design of Sustainable Hives and Trap Nests for Tetragonula iridipennis (Smith) in the Western Ghats, India - Imran Ali; R. N. Kencharaddi; Charanakumar; Chet P. Bhatta; S Dinesha (Sociobiology, 2025)
The stingless bee species Tetragonula iridipennis (Hymenoptera: Apidae: Meliponinae) is native to India’s Western Ghats, a biodiversity hotspot. It plays a critical role in pollination and ecosystem stability. This study aimed to develop suitable trap nests and hive designs for the sustainable maintenance of T. iridipennis by analyzing its natural nesting ecology and nest architecture. Seven trap nest designs and four hive types were evaluated based on parameters including brood size, the number of honey and pollen pots, honey pot segregation, brood temperature, and percentage increase in brood volume and storage pots. Among trap nests, reused Apis cerana hives performed best, followed by bamboo slits, wooden hives, and coconut shells. Hive design significantly influenced colony development. The rectangular box with two halves showed the highest brood volume and the greatest number of honey and pollen pots, while the rectangular box with two compartments had the lowest. However, honey pot segregation –important for hygienic honey harvesting – was observed only in the Utrecht University Tobago (UTOB) hive, which had two compartments. The best-performing design for colony growth lacked segregation. Brood temperature did not vary significantly across designs. These findings suggest the rectangular box with two halves is optimal for brood and resource production, but may not support clean honey harvesting. Future designs should combine the advantages of colony development and honey pot segregation. Such tailored hive models could support the conservation and sustainable beekeeping of T. iridipennis in the Western Ghats.